Bioactive chemical constituents of Curcuma longa L. rhizomes extract inhibit the growth of human hepatoma cell line (HepG2) - Abdel-Lateef Ezzat; Mahmoud Faten; Hammam Olfat; El-Ahwany Eman; El-Wakil Eman; Kandil Sherihan; Abu Taleb Hoda; El-Sayed Mortada; Hassenein Hanaa (Acta Pharmaceutica)
The present study was designed to identify the chemical constituents of the methanolic extract of Curcuma longa L. rhizomes and their inhibitory effect on a hepatoma cell line. The methanolic extract was subjected to GC-MS analysis to identify the volatile constituents and the other part of the same extract was subjected to liquid column chromatographic separation to isolate curcumin. The inhibition of cell growth in the hepatoma cell line and the cytopathological changes were studied. GC-MS analysis showed the presence of fifty compounds in the methanolic extract of C. longa. The major compounds were ar-turmerone (20.50 %), β-sesquiphellandrene (5.20 %) and curcumenol (5.11 %). Curcumin was identified using IR, 1H and 13C NMR. The inhibition of cell growth by curcumin (IC50 = 41.69 ± 2.87 μg mL-1) was much more effective than that of methanolic extract (IC50 = 196.12 ± 5.25 μg mL-1). Degenerative and apoptotic changes were more evident in curcumin- treated hepatoma cells than in those treated with the methanol extract. Antitumor potential of the methanolic extract may be attributed to the presence of sesquiterpenes and phenolic constituents including curcumin (0.051 %, 511.39 μg g-1 dried methanol extract) in C. longa rhizomes.